Star Wars : before the awakening - Rucka, Greg (Disney Lucasfilm Press, 2015)
Reveals the origins of a doubtful stormtrooper for the First Order called FN-2187, a young scavenger on the desert planet of Jakku who calls herself Rey, and a hotshot Republic pilot named Poe Dameron, before they become involved in the major conflicts disrupting the galaxy.